Eugenia caipora, a new species of Eugenia sect. Pseudeugenia (Myrtaceae) from northeastern Brazil - Lima Lourenço, Ana Raquel De; Costa-Lima, James Lucas Da; de Oliveira Chagas, Earl Celestino (Phytotaxa, 2019)
Eugenia caipora (Myrtaceae), a new species from northeastern Brazil, is here described; it occurs in restinga vegetation, Tabuleiros litorâneos (Tabuleiro savanna), and seasonal forests in Ceará, Rio Grande do Norte, Paraíba, Pernambuco and Alagoas. The new species is morphologically similar to Eugenia azuruensis, though differing by the leaf blades abaxially glabrous to puberulent (vs. densely tomentose in E. azuruensis), non-mucronate (vs. mucronate), with flat margins (vs. revolute), calyx lobes 4–5 mm wide (vs. 6–10 mm), rounded at the apex (vs. apiculate), and petals 5–15 mm long (vs. 20–24 mm). A table of diagnostic characters for the new and related species and photographs of morphological diagnostic characters are provided.